Concurrent Respiration Monitoring of Multiple Subjects by Phase-Comparison Monopulse Radar Using Independent Component Analysis (ICA) With JADE Algorithm and Direction of Arrival (DOA) - Islam, Shekh M. M.; Boric-Lubecke, Olga; Lubekce, Victor M. (IEEE access, 2020)
While non-contact monitoring of human respiration has been demonstrated using Doppler radar, the concurrent monitoring of multiple equidistant subjects remains a significant technological challenge. Reported research has so far been limited to maintaining 1-m subject separation, based on the radar antenna beam-width. Proposed here is a hybrid method consisting of an SNR-based intelligent decision algorithm which integrates two different approaches to isolate respiratory signatures of two subjects within the radar beam-width separated by less than 1 meter. Using Independent Component Analysis with the JADE algorithm (ICA-JADE) and Direction of Arrival (DOA), this SNR-based decision algorithm works with an accuracy above 93%. In addition, angular location of each subject is estimated by phase-comparison monopulse and an integrated beam switching capability is demonstrated to optimally extract respiratory information. The proposed method coherently combines two separation methods to overcome multiple-subject monitoring limits which can lead to practical adoption for many respiration monitoring applications.